Analisis Penilaian Kinerja Dengan Menggunakan Metode Balanced Scorecard Di Rumah Sakit Dr.Etty Asharto Batu - Kosasih, Maratus Sholihah Aprilia; Suprapti, Suprapti (University of Merdeka Malang, 2020)
Nowadays plenty of hospitals still applying traditional approach on their performance, which emphasized on Balanced Scorecard method. This research purposely made to evaluate the performance of Balanced Scorecard method on dr. Etty Asharto Hospital in Batu. There are two aspects evaluated, finance and non finance aspect, using perspectives of the customers’; internal business process’; educational and developments’; lastly finance’s as in the Balanced Scorecard perspective. The research’s information was taken from the finance data collection from 2014 to 2018. this research using descriptive analysis where the researcher evaluate the performance on dr. Etty Asharto Hospital in Batu by giving score based on the criteria on the 4 Perspectives of Balanced Scorecard and then analyzed to determine whether the score is good, enough, or bad. The instruments of the research are interview, questionnaire, and literature review as the primer and secondary variety. The sample was taken from 152 customers and the staff of dr. Etty Asharto Hospital in Batu.Based on the result of the research, it can be concluded that the performance of dr. Etty Asharto in Batu was scored to be enough, analyzed from the 4 Perspectives of Balanced Scorecard method. the performance scoring using Balanced Scorecard method in dr. Etty Asharto Hospital could be enforced in the future because the method could provide more structured also could widely relate and present the 4 Perspective of Balanced Scorecard better.. DOI: 10.26905/ap.v6i2.4277